Enhancement In strain hardening magnesia composites after autogenous healing - Ho, Christabel Jia Wen (Nanyang Technological University, 2021)
Strain Hardening Magnesia Composites (SHMC) has the capability to recover and enhance its mechanical properties after the self-healing process. SHMC have great self-healing potential and existing research shows very strong recovery after healing cycles. However, the recovery of the mechanical properties of SHMC has not been systematically researched. This paper investigates the enhancement of mechanical properties through the MgO-based strain hardening composites (SHC) with self-healing capabilities. Pre-loaded samples are cracked to specific strain levels of 0.5%, 1% and 1.5% which will then be put through healing regimes of wet-dry cycles with the different dry cycles of Lab Ambient Air, 0.5% CO2 and 10% CO2 for 15 cycles. Recovery and assessment of mechanical properties were done by resonant frequency tests, microscopy crack width measurements and uniaxial tensile test. Results show the effects of pre-strain levels and CO2 concentrations on the sample. Higher CO2 concentrations were able to show a high recovery rate and higher sealing of crack openings. Both the influence of pre-strain levels and CO2 concentrations affect mechanical performance. Findings show that higher pre-strain levels and higher CO2 concentrations were able to achieve higher ultimate tensile strength and strain capacity. Higher pre-strain levels induce more multiple cracks across the area of the sample which allows for healing to be evenly distributed across the sample. Higher CO2 concentrations enable higher reactivity and carbonation processes to heal the sample. With the high pre-strain levels and CO2 concentrations of the RMC-SHC, the mechanical properties show significant enhancement.